EKSPLORASI DAN SKRINNING BAKTERI PELARUT FOSFAT DARI KAWASAN TAMAN NASIONAL LORE LINDU - Salapu Pagiu (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
Exploration of phospate solubizing bacteria (PSB) was carried out to know the population density and diversity of PSB in any rhizospore of vegetation in the area of Lore-Lindu National Park.      The Rhizospore sampling used meyhod of ‘Polar Institu-Bromophenol Blue (NBRI-BPB), Pikovskaya media and Tadulako-2 media. The result showed that 52 isolates of bacteria had been differentiated from 25 rhizospere sample with population density range between 19.0 and 192.5 (x104 cfu g-1), yellow and white of colony colors, and colony diameter between 1.5 mm and 3.5 mm. Screening these bacteria in NBRI-BPB media found 25 isolates classified as phospate solubizing bacteria based on clear zone showed in media. The diameter of clear zone range between 3.0 mm and 4.5 mm. Continuing tested of these 25 PSB isolates showed that seven isolates clustered as superior PSB based on their ability to solve tricalsium phospate in liquid Pikovskaya media with phospate concentration range between 671.5 and 895.7 (mg L-1+ media). These isolates also showed better viability with population density rangr between 87.5 and 142.0 (x106 cfu g-1) after 80 days inoculated in Tadulako-2 media. These seven isolates were SED-01, WUA-07, KAD-08, WAN-03, WAT-03, TAL-02, and ROM-05. Key Words : Exploration, NBRI-BPB, phospate solubizing bacteria, polar sampling plans, tadulako-2 media.